NATIVE AMERICAN REPRESENTATION IN SHERMAN ALEXIE’S SHORT STORY THE TRIAL OF THOMAS BUILDS-THE-FIRE - Mike Wijaya Saragih (DIALEKTIKA: JURNAL BAHASA, SASTRA DAN BUDAYA, 2021)
Abstract This paper aims to show the representation of Native Americans in Sherman Alexie's short story The Trial of Thomas-Builds-the-Fire, which is part of his story collections The Lone Ranger and Tonto Fistfight in Heaven (1993). The main character, Thomas-Builds-the-Fire, represents native Americans. This paper will analyze Thomas as a subaltern who was oppressed by white hegemony. The presence of fairy tales as media voicing out Thomas' thoughts and feeling as the subaltern interprets something deeper. The present writer will use Gayatri C. Spivak's theories which are subaltern and representation, to analyze the forms of Native American representation. The result shows there are two forms of representation used in the story. They are "to represent," meaning "the idea of representing something," and "re-present," meaning "the idea of bringing back." However, both forms of representation stated in the story failed to make the subaltern speak or be heard. Kata kunci: fairy tales, Native American, representation, subaltern Abstrak Tulisan ini bertujuan untuk menunjukkan representasi penduduk asli atau pribumi Amerika dalam cerpen Sherman Alexie yang berjudul The Trial of Thomas-Builds-the-Fire, yang merupakan bagian dari buku kumpulan cerita pendek karya Sherman Alexie yang berjudul The Lone Ranger dan Tonto Fistfight in Heaven (1993). Penduduk asli atau pribumi Amerika direpresentasikan oleh tokoh utama Thomas-Builds-the-Fire. Tulisan ini akan berfokus pada Thomas sebagai subaltern yang tertindas oleh hegemoni kulit putih. Kehadiran dongeng sebagai media yang menyuarakan pikiran dan perasaan Thomas sebagai subaltern memaknai sesuatu yang lebih dalam. Untuk menemukan bentuk-bentuk representasi penduduk asli atau pribumi Amerika akan diterapkan konsep Subaltern dan Representasi oleh Gayatri C. Spivak. Hasil dari penelitian ini adalah ditemukannya dua bentuk representasi di dalam teks, yaitu representasi (represent) sebagai “yang mewakili” dan representasi (re-present) sebagai “yang menghadirkan kembali”. Kedua bentuk representasi yang muncul di dalam teks gagal membuat subaltern bersuara maupun didengar. Keywords: dongeng, pribumi Amerika, representasi, subaltern